A Nomogram utilizing ECG P-wave parameters to predict recurrence risk following catheter ablation in paroxysmal atrial fibrillation - Li-juan Yu; Xue-Hai Chen; Zhe Xu; Ke-Zeng Gong; Fei-Long Zhang (Journal of Cardiothoracic Surgery)
Highlights Abnormal changes in P-wave parameters indicative of atrial electrical remodeling often manifest earlier than changes in other indicators reflecting atrial structural remodeling in paroxysmal atrial fibrillation. Preoperative absolute values of Maximum P Wave Duration, P Wave Dispersion, and P Wave Terminal Force of V1, as well as postoperative absolute values of Maximum P Wave Duration, P Wave Duration, P Wave Dispersion, P Wave Terminal Force of V1, and P Wave Area, demonstrate strong predictive value for recurrence risk of paroxysmal atrial fibrillation after Catheter Ablation. The nomogram model based on P-wave parameters before and after catheter ablation exhibits notably strong predictive performance and offers significant clinical benefits.